Government Finance Statistics Yearbook, 2012. (Government Finance Statistics; Government Finance Statistics ;, 2013)
The demand for high quality detailed public finance statistics covering a globally representative sample of countries has increased dramatically during the recent financial crisis. Due to the complexity of public finance statistics, however, such data tend to be either available in oversimplified high level aggregates and lacking in methodological transparency, or, available with a great level of detail and a unified methodological approach yet overly complicated to understand. The IMF's Government Finance Statistics Yearbook shows fiscal data of around 140 countries following the Government Finance Statistics Manual 2001 framework. The associated database includes data series covering over an almost 40 year period. The IMF's Statistics Department embarked on several initiatives to improve its accessibility.